Detection of the agr System and Resistance to Antimicrobials in Biofilm-Producing S. epidermidis - Cataneli Pereira, Valéria [UNESP]; Pinheiro-Hubinger, Luiza [UNESP]; de Oliveira, Adilson [UNESP]; Moraes Riboli, Danilo Flávio [UNESP]; Benini Martins, Katheryne [UNESP]; Calixto Romero, Letícia [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (MDPI, 2020)
The ability of Staphylococcus epidermidis to produce virulence factors, such as biofilm, added to its increased resistance to antimicrobials can cause infections that are difficult to treat. Many staphylococcal virulence factors are under the control of the accessory gene regulator (agr). The objective of this study was to establish the agr locus and susceptibility of biofilm-producing S. epidermidis specimens to antimicrobial agents, through PCR reactions, reverse transcription polymerase chain reaction (RT-PCR), and the determination of minimum inhibitory concentration (MIC), and to analyze the clonal profile of 300 strains isolated from blood culture specimens from inpatients at a University Hospital in Brazil, over a 20-year period by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) techniques. The ica operon expression was shown in 83.6% strains, bhp gene in 11.5%, and aap gene in 32.8%. Oxacillin resistance was detected in 90.1%, while 4.9% showed tigecycline resistance, and intermediate resistance to quinupristin/dalfopristin was identified in 0.4%. Clonal profile determination showed 11 clusters, with the ST2 type determined as the major cluster. The S. epidermidis biofilm producer demonstrated a predominance of agr I locus, oxacillin resistance, and SCCmec III as well as the potential dissemination of pathogenic clones in hospital settings over long periods.
Keywords: agr locus; antimicrobial resistance; biofilm; oxacillin resistance; ST2